Factors associated with potentially harmful antibiotic prescription during pregnancy: a population‐based study. Issue 2 (8th October 2015) - Lee, Yichen; Chen, Chuchieh; Chu, Dachen; Ko, Mingchung
Abstract: Rationale, aims and objectives: Inappropriate antibiotic prescriptions during pregnancy may adversely affect the fetus. There were few studies on factors associated with antibiotic prescriptions potentially harmful to the fetus. Methods: This was a population‐based cross‐sectional study using data from National Health Insurance Research Database. We calculated the frequency of antibiotic prescription according to the status of pregnancy, type of infections, characteristics of patients, doctors and medical institutions. According to the British National Formulary, sulfonamides, trimethoprim, tetracycline and quinolones were classified as antibiotics potentially harmful to the fetus. A multivariate logistic regression analysis was performed to evaluate the independent effect of various characteristic on antibiotic prescriptions, during pregnancy, potentially harmful to the fetus. Results: Among the 19 464 pregnant subjects, 6554 (33.67%) received antibiotic prescriptions during pregnancy. Antibiotic prescriptions potentially harmful to the fetus accounted for 6.31% of all antibiotic prescriptions during pregnancy. Pregnant women aged <20 years, in their first trimester, and who were presenting with urogenital infections had the highest risks of receiving antibiotic prescriptions potentially harmful to the fetus. Non‐gynaecologists, doctors aged 39–49 or ≥50 years, and doctors at clinics had higher risks of prescribing antibiotics potentially harmful to the fetus. Conclusions: Measures to improve the quality of practices should include efforts to increase awareness of antibiotic prescription guidelines for the treatment of infections in the pregnant population.